KONSTRUKSI CITRA JOKO WIDODO DAN PRABOWO SUBIANTO DI DALAM PEMBERITAAN HARIAN BERBAHASA JEPANG THE DAILY JAKARTA SHINBUN PADA MASA KAMPANYE PEMILIHAN PRESIDEN INDONESIA 4 JUNI – 5 JULI 2014 - Moh Gandhi Amanullah (Universitas Airlangga, 2016)
Jakarta Shinbun is one of the largest, and the only Japanese language dailynewspaper published in Indonesia. The head office is located in Jakarta and all of the editorial teams are Japanese journalists. Reader target of this daily are Japanese people living in Indonesia. Therefore, it could be predicted that it has a strong influence in shaping public opinion among Japanese living in Indonesia. At the time of Indonesian presidential election campaign from June 4 to July 5, 2014, Jakarta Shinbun (JS) published so many articles about campaign of two Indonesian presidential candidates, namely: Joko Widodo and Prabowo Subianto. This study aims to examine how the images of Joko Widodo and Prabowo Subianto were constructed in the news of Jakarta Shinbun during the presidential campaign. There are 56 articles to be examined, and to analyze them, the used methods are quantitative and qualitative approach by applying media content analysis, and discourse analysis. The result is known Prabowo Subianto was negatively imaged than Jokowi during the presidential election campaign of 2014. So it can be interpreted as well that this newspaper supported Joko Widodo more than another candidate during presidential election campaign.